The Role of Apparent Diffusion Coefficient in Differentiating Benign and Malignant Endometrial Pathologies: A Prospective Single-Center Study - Sherwani, Poonam; Nandolia, Khanak; Chawla, Latika; Kumar, Arvind; Syed, Anjum; Kumari, Ranjeeta (Indian Journal of Radiology and Imaging, 2025)
To investigate the added role of apparent diffusion coefficient (ADC) in differentiating benign from malignant pathologies.Hospital-based random sampling was done and all the females with clinical details suggestive of endometrial pathologies and abnormal ultrasound underwent contrast-enhanced magnetic resonance imaging (MRI). In addition to the routine sequences, imaging was done at different b-values and ADC was calculated. The higher the ADC value the more the chances of benignity. Dynamic contrast-enhanced imaging was also done. Two radiologists with 18 and 10 years of experience evaluated the imaging findings and interobserver agreement was also made. Imaging findings were correlated with diagnosis as made by endometrial aspirate biopsy, dilatation–curettage, or postoperative histopathological examination.The addition of ADC value and dynamic contrast-enhanced MRI showed a significant role in differentiating benign from malignant conditions. The mean ADC measurement in malignant lesions was 0.88 × 10−3 ± 0.27 × 10−3, whereas the mean ADC measurement for benign lesions was 1.03 × 10−3 ± 0.38 × 10−3. The differences between the two were found to be significant (t-value: 2.754, p-value: 0.014). The cutoff of mean ADC and minimum ADC with the highest sensitivity and specificity were reported to be ≤1 × 10−3 and ≤0.8 × 10−3, respectively.Adding the ADC value with routine magnetic resonance sequences plays a significant role in differentiating between benign and malignant endometrial pathologies, especially in indeterminate cases
Keywords: apparent diffusion coefficient; endometrium; histopathology; magnetic resonance imaging